Evaluation of in vitro activity of Calvatia craniiformis extract against bacteria isolated from pregnant women with asymptomatic bacteriuria - Motib, Anfal Sh.; Ibrahim, Basim M.; Rahid, Hiba H. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Urinary tract infection (UTI) is the most common disease associated with pregnant women due to several anatomical and hormonal changes in pregnant women lead to ureteral dilatation and urinary infection, many of microorganisms such as fungi, viruses, and bacteria have numerous virulence factors that enhance their ability to colonize in pregnant women. Some bacteria have resistance toward many antimicrobial agents for treatment has led to therapeutic difficulties worldwide, in order that many investigators try to test fungal extract to reduce bacterial infection. Objectives: To assess the effectiveness of extract of Calvatia craniiformis on different types of bacteria which was isolated from pregnant women with asymptomatic bacteriuria. Materials and methods: One hundred five vaginal swabs were collected from pregnant women with asymptomatic bacteriuria attending to Al-Batool hospital for maternity and children in Diyala Governorate during the period from 1st /April /2012 till 1st/ July/2012. All specimens were streak on blood agar and MacConke ager, then identified according to standard bacteriology and biochemical criteria. The susceptibility patterns toward 6 antimicrobial agents were done by disc diffusion methods, 40% Calvatia craniiformis extract used for study the effect of this extract against different types of bacteria . Results: Fifty fife out of 105 samples (52.38%) were demonstrated negative bacteria growth while 50 out of 105 samples (47.61%) demonstrated positive bacteria culture. The isolated revealed that 22 Escherichia coli, 15 Klebsiella, 11 Proteus, and 2 Staphylococcus saprophetec. The majority of bacterial isolates were sensitive to 40% concentration of extract of Calvatia craniiformis. Conclusion: Extract of Calvatia craniiformis was effective as antibacterial against antibiotic resistant strain.